Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inlet Flow Field Conditions on the Performance of Centrifugal Compressor Diffusers: Part 1 — Discrete-Passage Diffuser

Abstract: This is Part 1 of a two-part paper considering the performance of radial diffusers for use in a high performance centrifugal compressor. Part 1 reports on discrete-passage diffusers (shown in Fig. 1) while Part 2 describes a test of a straight-channel diffuser designed for equivalent duty. Two builds of discrete-passage diffuser were tested, with 30 and 38 separate passages. Both the 30 and 38 passage diffusers investigated showed comparable range of unstalled operation and similar level of overall diffuser pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Hence, we can expect the diffuser static pressure recovery to be affected by the flow non-uniformity at impeller exit. Filipenco et al [2000] and Deniz et al [2000] showed that mass-averaged stagnation pressure at diffuser inlet is satisfactory in correlating the diffuser pressure recovery. Based on the above considerations, it is appropriate to express the results on a mass average basis.…”
Section: Conceptual Choices For Averaged Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we can expect the diffuser static pressure recovery to be affected by the flow non-uniformity at impeller exit. Filipenco et al [2000] and Deniz et al [2000] showed that mass-averaged stagnation pressure at diffuser inlet is satisfactory in correlating the diffuser pressure recovery. Based on the above considerations, it is appropriate to express the results on a mass average basis.…”
Section: Conceptual Choices For Averaged Resultsmentioning
confidence: 99%
“…Philips [1997], Filipenco et al [2000] and Deniz et al [2000] showed that vaned diffuser channel performance is weakly dependent on inlet blockage, but strongly affected by momentum-averaged flow angle. The three authors used the following definition for the momentum-averaged flow angle:…”
Section: Conceptual Choices For Averaged Resultsmentioning
confidence: 99%
“…The CFD data further support the correlation, with the same exception as observed earlier for the cases with low average diffuser inflow angles. As observed by Filipenco and Deniz [3,4], the emphasis placed on blockage in typical approaches to the analysis of vaned diffusers appears misplaced. Mixing occurs through the vaneless space between impeller and diffuser; CFD data shows that, for the peak efficiency point at the design corrected speed, the non-uniformity in mass flux reduces by 7% from impeller trailing edge to the diffuser trailing edge.…”
Section: Effect Of Time-average Mach Number and Flow Anglementioning
confidence: 99%
“…This total temperature ( ) probe comprises a 0.81 mm tube with two aligned holes drilled radially through the tube. The first hole, 0.46 mm in diameter, is rotated to face 3 The work done by the swirl rig rotor is low, resulting in total temperature ratios below 1.15. The assumption of uniform total temperature is fair.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation